Effect of CYP3A perpetrators on ibrutinib exposure in healthy participants. Issue 4 (24th June 2015) - de Jong, Jan; Skee, Donna; Murphy, Joe; Sukbuntherng, Juthamas; Hellemans, Peter; Smit, Johan; de Vries, Ronald; Jiao, Juhui James; Snoeys, Jan; Mannaert, Erik
Abstract Ibrutinib (PCI‐32765), a potent covalent inhibitor of Bruton's tyrosine kinase, has shown efficacy against a variety of B‐cell malignancies. Given the prominent role of CYP3A in ibrutinib metabolism, effect of coadministration of CYP3A perpetrators with ibrutinib was evaluated in healthy adults. Ibrutinib (120 mg [Study 1, fasted], 560 mg [studies 2 (fasted), and 3 (nonfasted)]) was given alone and with ketoconazole [Study 1; 400 mg q.d.], rifampin [Study 2; 600 mg q.d.], and grapefruit juice [GFJ, Study 3]. Lower doses of ibrutinib were used together with CYP3A inhibitors [Study 1: 40 mg; Study 3: 140 mg], as safety precaution. Under fasted condition, ketoconazole increased ibrutinib dose‐normalized (DN) exposure [DN‐AUClast: 24‐fold; DN‐Cmax: 29‐fold], rifampin decreased ibrutinib exposure [Cmax: 13‐fold; AUClast: 10‐fold]. Under nonfasted condition, GFJ caused a moderate increase [DN‐Cmax: 3.5‐fold; DN‐AUC: 2.2‐fold], most likely through inhibition of intestinal CYP3A. Half‐life was not affected by CYP perpetrators indicating the interaction was mainly on first‐pass extraction. All treatments were well‐tolerated.